Radical evil and the invisibility of moral worth in kant's die religion (2007)
There is an aporia in Kant’s analysis of evil: he defines radical evilas an invisible disposition of the will, but he also demands an inferential connection between visible evil actions and this invisible disposition. This inference, however, undermines the radical invisibility of radical evil according to Kant’s own definition of the latter. Noting how this invisibility of moral worth is a distinctive feature of Kant’s approach to the moral problem, the paper then asks why, in the Groundwork, he nonetheless forecloses a question about evil that seems to be consistent with this approach. It is argued that to account for this aporia and this foreclosure, one has to interrogate the way in which the category of religion orients Kant’s incipient philosophy of history in Die Religion.